Metabolic syndrome criteria and its association with type 2 diabetes and cardiovascular diseases - Yadav, Dhananjay; Puranik, Nidhi; Sen, Amit; Mishra, Meerambika; Kwak, Minseok; Jin, Jun-O (Progress in Nutrition, 2020)
Metabolic syndrome is a cluster of metabolic anomalies such as insulin resistance, obesity, abdominal fat deposition, hypertension and dyslipidemia, which put an individual at a higher risk of developing cardiovascular complications. Global variation in ethnicity, culinary habits, availability of nutritious elements, lifestyle, economic status and disease tolerance/susceptibility of the workforce is reflected in the definition of the syndrome given by various public health entities. The present review summarizes the recent advances in the understanding of metabolic syndrome which has been discussed at length by different organizations. A greater insight into diagnostic criteria of metabolic syndrome will improve our understanding and more importantly enable the prevention and management of this complex condition.